2014
DOI: 10.1096/fj.13-247015
|View full text |Cite
|
Sign up to set email alerts
|

Human biliverdin reductase‐based peptides activate and inhibit glucose uptake through direct interaction with the kinase domain of insulin receptor

Abstract: Insulin binding changes conformation of the insulin receptor kinase (IRK) domain and initiates glucose uptake through the insulin, IGF-1, phosphatidyl inositol 3-kinase (PI3K), and MAPK pathways; human biliverdin reductase (hBVR) is an IRK substrate and pathway effector. This is the first report on hBVR peptide-mediated IRK activation and conformational change. (290)KYCCSRK, which increased IRK V(max) without changing K(m), stimulated glucose uptake and potentiated insulin and IGF-1 stimulation in 4 cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 42 publications
2
57
0
Order By: Relevance
“…A potential inducer of bilirubin and HO-1 is the peptide derived from the human biliverdin reductase protein 221 . This peptide, as well as the L-4F (ApoA-1 mimetic) peptide, could have a powerful effect on the induction of HO-1, with a reduction of fatty liver insulin resistance and adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…A potential inducer of bilirubin and HO-1 is the peptide derived from the human biliverdin reductase protein 221 . This peptide, as well as the L-4F (ApoA-1 mimetic) peptide, could have a powerful effect on the induction of HO-1, with a reduction of fatty liver insulin resistance and adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…However, later investigations showed that siRNA suppression of BVRA increased pAkt in HK-2 proximal tubule epithelial human cells (41), human macrophages (40) and rat heart H9c2 cells (39), suggesting that BVRA may positively affect glucose uptake. The duality of BVRA on insulin signaling was further highlighted in a recent study using different peptide sequences of BVRA (8). The terminal 290 KYCCSRK peptide was found to increase glucose uptake and potentiate insulin, while a peptide ( 194 KEDQYMKMTV) corresponding to BVRA's SH2-binding domain was a potent inhibitor of glucose uptake and insulin signaling (8).…”
Section: Biliverdin Reductase and Insulin Signaling Pathwaysmentioning
confidence: 93%
“…The insulin signaling cascade diverges into two major arms, the PI3-kinase/Akt, and the IRK/IRS/PI3-kinase/MAPK pathway. BVRA but not BVRB is known to interact with components in both pathways, and thus may have a role in the regulation of metabolic processes (Figure 3) (8, 18). …”
Section: Biliverdin Reductase and Insulin Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations